Use of electric resistivity tomography (ERT) for detecting underground voids on highly anthropized urban construction sites. (2017) - Ungureanu, Constantin; Priceputu, Adrian; Bugea, Adrian Liviu; Chirică, Anton
Abstract: The current paper presents the use of ERT geophysical investigations performed on a construction site to investigate the presence of underground voids (old basements, embedded pipes etc.) that can cause safety and technological issues during future construction works. The data acquisition was based on 4 ERT profiles placed along the area were underground voids were expected. Some acquisition and processing challenges were encountered and the applied solutions are presented herein. The anomalies presented on profiles recorded with different electrode arrays (Wenner, Schlumberger, Dipole-Dipole) show the presence of underground voids, but the position and size cannot be determined exactly, so a reliability based approach is employed to characterize the result.